Antimicrobial Susceptibility of Stenotrophomonas maltophilia Clinical Isolates from Blood Samples in Iran - Amir Hesam Nemati; Hamid Solgi; Farzam Vaziri; Fereshteh Shahcheraghi (Journal of Medical Microbiology and Infectious Diseases, 2015)
Introduction: Stenotrophomonas maltophilia is a nosocomial multi drug resistant opportunistic pathogen which causes infections in vulnerable patients with cancer, cystic fibrosis and indwelling catheters. Methods: 45 clinical S. maltophilia isolates were collected from blood samples and identified by biochemical tests. Susceptibility to different antibiotics including co-trimoxazole, levofloxacin, minocycline, ticarcillin/clavulanic acid, chloramphenicol and ceftazidime were determined by disk diffusion and E-test methods. Results: All isolates were resistant to ceftazidime and susceptible to co-trimoxazole and  11.1% were resistant to ticarcillin/clavulanic acid. Conclusion: Ceftazidime as one of the extended spectrum β-lactams was the least effective antibiotic. Ticarcillin/clavulanic acid is one of the choosen antibiotics for S. maltophilia infections treatment. Here, we report tcarcillin/clavulanic acid resistance in S. maltophilia isolates for the first time in Iran.